Sistema de controle ativo inibidor de lesões por pressão - (:unkn) unknown (Universidade Federal de Goiás, 2017)
At the treatment sites of people who are bedridden, usually in Intensive Care Units, Long-Term Care Facilities for the Elderly and in the home environment due to the diffusion of home care, the incidence of Pressure Injury (LPP) is common. In order to reduce suffering and increase the life expectancy of patients with this problem, alternative methods are needed that can be introduced into the care of nursing teams to achieve the eradication or minimization of LPP. This paper presents a proposal of an innovative and low cost solution for LPP prevention. Applying concepts of automation and control, through existing technologies and low-cost components, the development of a device is developed that aims to assist the medical team and all those who have the responsibility of caring for individuals bedridden in LPP care. The device consists of pressure, humidity and temperature sensors, with a consequent real-time performance on these three variables at points with a higher probability of involvement of LPP.
Active control system inhibitor of pressure injury
Keywords: Automação; Pneumática; Eletrônica; Lesão por pressão; Tecnologia assistiva; Automation; Pneumatics; Electronics; Pressure injury; Assistive technology; BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS